Zintegrowana kampania badawcza dla określenia ekologicznego stanu zbiornika retencyjnego "Jezioro Turawskie" zgodnie z zasadami zrównoważonego rozwoju = The integrated research campaign for determination of ecological state of the storage reservoir "Jezioro Turawskie" in accordance to the rules of balanced development - Gurwin, Jacek; Kryza, Józef; Poprawski, Lech; Skowronek, Artur (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The basic aims of multidisciplinary Turawa Lake Project are presented in the paper. The project is focused on ecological condition of the reservoir. The Turawa Lake is undergoing rapid anthropogenic eutrophication, that's why the priority in investigations is given to assessing the pollution and to choose an effective method of remediation of the reservoir. The groundwater and surface water monitoring system has been developed and sediment samplingcampaign as well to obtain sufficient data.
Keywords: 3 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: zrównoważona gospodarka zasobami naturalnymi" (24-25.06.2004)